Youth Demographic Characteristics and Risk Perception of Using Alternative Tobacco Products: An Analysis of the 2014-2015 Canadian Student Tobacco, Alcohol, and Drugs Survey (CSTADS) - Udoka Okpalauwaekwe MBBS, MPH; Chinenye Nmanma Nwoke BSc, MPH; Jacinthe Messier BSc, MSc (SAGE Publishing, 2021)
Background There is a growing attraction by youth to alternative tobacco products (ATPs) such as e-cigarettes and hookahs. This study investigated risk perceptions and demographic characteristics associated with ATP use in grade 8-10 students. Methods Data were drawn from the 2014/15 cycle of the CSTADS. The analytic sample included 1819 students from a total pool of 42 094 students who completed the survey. Logistic regression models were used to examine factors (demographic characteristics and risk perception) associated with ATP use in the past 30 days. Results 12% of students in grade 8-10 self-identified as having used ATPs in the past 30-days, with a majority of students in grade 10 (56%). Male students had higher odds of reporting ATP use when compared to females. Although a lesser proportion of Indigenous students reported ATP use in comparison to White students (31% vs 61%), Indigenous students were 2.42 (1.49, 3.93) times as likely to use ATPs as White students. Students who perceived smoking hookah once in a while as "no to slight risk" were 1.58 (1.09, 2.28) times more likely to report ATP use than students who perceived "moderate to great risk." Also, students who perceived using e-cigarettes on a regular basis as "no to slight risk" were 2.21 (1.53, 3.21) times more likely to report ATP use as students who perceived "moderate-great risk." Conclusion A significant number of grade 8-10 students use ATPs, especially e-cigarettes, with the misconception of minimal health risks. There remains the need to do more to counteract the rise in social and epidemiological alternative tobacco use trends among the youth.